2016
DOI: 10.1101/061606
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A systematic comparison reveals substantial differences in chromosomal versus episomal encoding of enhancer activity

Abstract: Candidate enhancers can be identified on the basis of chromatin modifications, the binding of chromatin modifiers and transcription factors and cofactors, or chromatin accessibility. However, validating such candidates as bona fide enhancers requires functional characterization, typically achieved through reporter assays that test whether a sequence can increase expression of a transcriptional reporter via a minimal promoter. A longstanding concern is that reporter assays are mainly implemented on episomes, wh… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
170
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(183 citation statements)
references
References 60 publications
13
170
0
Order By: Relevance
“…We demonstrate that (i) the PPARγ motif affinity (and not cooperative elements in the immediately flanking sequence) largely determines PPARγ binding to genomic sequences when removed from their chromatin context; (ii) enhancer activity depends not only on PPARγ binding but also on a network of 20-30 TF motifs in the flanking sequence that have distinct quantitative contributions to expression; and (iii) various pairs of motifs interact in additive, inhibitory, and synergistic ways with varying constraints on motif positioning. Although in this study we measured enhancer activity in an episomal context, a recent study found that enhancer activity was highly concordant between episomal and genomic contexts (r = 0.86 across 2,236 candidate enhancers vs. 0.90-0.98 for replicates within each context) (93). Importantly, our results show that PPARγ binding and enhancer activity are independently regulated.…”
Section: Discussionmentioning
confidence: 65%
“…We demonstrate that (i) the PPARγ motif affinity (and not cooperative elements in the immediately flanking sequence) largely determines PPARγ binding to genomic sequences when removed from their chromatin context; (ii) enhancer activity depends not only on PPARγ binding but also on a network of 20-30 TF motifs in the flanking sequence that have distinct quantitative contributions to expression; and (iii) various pairs of motifs interact in additive, inhibitory, and synergistic ways with varying constraints on motif positioning. Although in this study we measured enhancer activity in an episomal context, a recent study found that enhancer activity was highly concordant between episomal and genomic contexts (r = 0.86 across 2,236 candidate enhancers vs. 0.90-0.98 for replicates within each context) (93). Importantly, our results show that PPARγ binding and enhancer activity are independently regulated.…”
Section: Discussionmentioning
confidence: 65%
“…To disentangle both activities, we developed a new dual transgenic assay that can measure enhancer and promoter activity at the same genomic location in the same embryos such that the timing as well as tissue specificity of both activities can be directly compared. Transgenic assays have the advantage of being able to measure regulatory activity at the endogenous levels of TFs and within a consistent chromatinized context-two properties that have a major impact on both enhancer and promoter activity (Archer et al 1992;Jeong and Stein 1994;Hebbar and Archer 2008;Inoue et al 2017). The readout (in situ hybridization) provides both spatial and temporal information at single-cell resolution, although it is difficult to derive quantitative information on activity-a clear disadvantage compared with in vitro reporter assays.…”
Section: Intergenic Embryonic Enhancers Can Function As Weak Promotersmentioning
confidence: 99%
“…However, these assays function outside of a normal chromatinized context, an important property known to affect both promoter (transcriptional initiation) (Archer et al 1992) and enhancer (Inoue et al 2017) activity through various mechanisms (Jeong and Stein 1994;Hebbar and Archer 2008). We therefore set out to assess the ability of enhancers to act as promoters in vivo in transgenic embryos using a stably integrated reporter that does not contain a core promoter.…”
Section: Highly Transcribed Developmental Enhancers Have Weak Promotementioning
confidence: 99%
“…Currently, most experimental strategies rely on reporter assays that assess regulatory function of variants using very artificial systems that investigate sequences outside of their native chromosomal context 34 . There are, however, new methods, such as using lentiviral based reporter assays that integrate into the genome that are very promising 107 . Additionally, CRISPR/Cas9 based genome-editing approaches that allow one to modify individual variants in human cells are becoming more efficient and will likely to play a large role in causal variant and gene discovery moving forward 108,109 .…”
Section: Future Directionsmentioning
confidence: 99%